The influence of cadmium on the photovoltaic performance of CoOx-based MAPbI3 solar cells - Alishah, Hamed Moeini (SPRINGER HEIDELBERG, 2024)
Perovskite-based solar cells have earned significant interest for more than a decade because of the distinctive properties they possess. Charge transport layers (CTL) play a critical role in the operation of perovskite solar cells. Consequently, selecting an appropriate and cheap CTL is paramount of importance. Though cobalt oxide shows great potential as a hole-injecting layer (HIL) for inverted PSCs, CoOx still needs to fulfill solar cell performance criteria. In this work, the PV operation of sol-gel-based MAPbI(3) PSCs has been shown to be enhanced by the incorporation of Cd to CoOx precursor. Further, doped film contributed to reducing the trap density of perovskite film. Thus, it is essential to determine the trap states that occur through the development of perovskites in order to get superb and prolonged performance. Cd-doped CoOx film showed an enhancement in electrical conductivity and hole mobility in comparison with pure CoOx which consequently, resulted in an enhancement of %22 PCE and better stability as well.
Keywords: Cobalt oxide; Perovskite; Cd doping; MAPbI(3); CTL; HOLE-TRANSPORT LAYERS; DOPED NICKEL-OXIDE; EFFICIENCY; COBALT; FILMS; ENERGY; CARBON; ZINC; Materials Science; Physics